1995
DOI: 10.1080/02652039509374326
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin adsorbent capacity of two Mexican aluminosilicates in experimentally contaminated chick diets

Abstract: To study the aflatoxin-adsorbent capacity of two Mexican aluminosilicates (ALS) identified as Atapulgita (AT) and Füller earth (FE), these ALS were compared with a commercial aluminosilicate, Novasil (NV), at two concentrations (0.05 and 1.0%) added to chick diets with 55% of experimentally contaminated corn (200 micrograms/kg). Eight treatments were studied with two replicates for treatment and four chicks per cage. Results (weight gain, feed efficiency, gross and microscopic pathology) at 3 weeks showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Similarly, (33) reported a significant decrease in the relative weight of the bursa of Fabricius when birds were exposed to diets having 2 ppm AF. Similar reduction in bursal relative weight and moderate histopathological changes have been reported in broilers (34), when birds were fed diets having various levels of AF (100 to 500 ppb).…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, (33) reported a significant decrease in the relative weight of the bursa of Fabricius when birds were exposed to diets having 2 ppm AF. Similar reduction in bursal relative weight and moderate histopathological changes have been reported in broilers (34), when birds were fed diets having various levels of AF (100 to 500 ppb).…”
Section: Discussionsupporting
confidence: 77%
“…The proposed mechanism of action is through the adsorption of AFs (mainly onto the interlayer spaces of montmorillonite) in the gastrointestinal tract of animals and humans, thus reducing toxin bioavailability to the blood and organs (Phillips, 1999). Bentonite clays, which are rich in montmorillonite, have been effectively used in dairy cows (Diaz et al, 2004; Harvey et al, 1991; Kutz et al, 2009), goats (Smith et al, 1994) and several other animal species (Harvey et al, 1994; Ledoux et al, 1999; Márquez and Hernandez, 1995; Phillips et al, 1990) to diminish the negative effects of AF exposure. Importantly, findings from a recent clinical intervention study showed that a montmorillonite rich Ca-bentonite (NovaSil-Plus, NS) was effective in reducing AF biomarkers in serum and urine with negligible nutrient interactions in humans naturally exposed to AFs via contaminated foods (Afriyie-Gyawu et al, 2008b; Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to sorb aflatoxin B 1 with high affinity and high capacity in aqueous solutions and was shown to rescue broiler and Leghorn chicks from the toxic effects of 7500 ppb aflatoxin in the diet (Phillips et al , 1988(Phillips et al , 2006. In subsequent studies, NS and other similar montmorillonite and smectite clays have been reported to protect against aflatoxin toxicity in a variety of young animals including rodents, chicks, turkey poults, ducklings, lambs, pigs, mink and trout (Phillips 1999;Phillips et al 1990Phillips et al , 1991Phillips et al , 1994Phillips et al , 1995Colvin et al 1989;Bonna et al 1991;Harvey et al 1991aHarvey et al , 1991bVoss et al 1993;Kubena et al 1990aKubena et al , 1990bKubena et al , 1991Kubena et al , 1993Ledoux et al 1999;Smith et al 1994;Marquez and Hernandez 1995;Cerdchai et al 1990;Lindemann et al 1993;Abdel-Wahhab et al 1998;Nahm 1995;Jayaprakash et al 1992;Ellis et al 2000). In studies using radiolabelled aflatoxins, NS clay has also been shown to decrease the bioavailability of aflatoxins and reduce aflatoxin residues in poultry (Davidson et al 1987;Jayaprakash et al 1992), rats Mayura et al 1998) and pigs (Beaver et al 1990).…”
Section: Chemopreventive Agentsmentioning
confidence: 99%